CONCEPTS OF UNDERSTANDING GEOLOGY AND NATURE - Norinov Fakhriyor Kurbonovich (American Journals, 2023)
"In our days, a person is not considered enlightened unless he is interested in natural science. Any objection that lacks sufficient interest in the field of electricity and stratigraphy (that is, a branch of geology) betrays an incomplete understanding of human life. The fact is that science is not only about gathering information about stratigraphy (department of geology) and the like, but it is an important factor that provides mental activity in our days. Anyone who does not fully understand these movements will be deprived of participation in the most important realities in the history of human activity. It is also inevitable that the history of ideas and advanced ideas cannot exist without the history of scientific ideas.